Risk Based bank rating and financial performance of Indonesian commercial banks with GCG as intervening variable - Andini Nurwulandari; Hasanudin Hasanudin; Bambang Subiyanto; Yulia Catur Pratiwi (Cogent Economics & Finance)
This study aims to analyze the effect of the financial health of Indonesian commercial banks on financial performance with good corporate governance as an intervening variable. This study utilizes the risk-based bank rating (RBBR) method with secondary data by examining annual reports of 41 commercial banks taken as samples for the period from 2014 to 2019. The ratios used in this study are Non-Performing Loans (NPL), Loan Deposit Ratio (LDR), Net Interest Margin (NIM), and Operating Efficiency Ratio (OER), Capital Adequacy Ratio (CAR), Return on Assets (ROA) and Good Corporate Governance (GCG). The results showed that NIM had a direct positive and significant effect on ROA, while OER had a negative and significant effect on ROA, as hypothesized. Direct testing of GCG shows a negative and significant effect of NPL and OER, as well as a positive and significant effect of NIM. Furthermore, indirect testing with intervening variables shows that GCG is able to mediate the relationship between NPL and OER on the financial performance of conventional banks in Indonesia. In addition, GCG is also empirically proven to strengthen the positive and significant effect of NIM on ROA. This finding underscores the importance of good corporate governance in improving the financial health of commercial banks in Indonesia. In addition, the results theoretically would imply for the relevance of investigations regarding governance mechanisms and moral ethics as the domains of strategic issues of corporate governance.